Domestic Constraints, Firm Characteristics, and Geographical Diversification of Firm-Level Manufacturing Exports in Africa - Yoshino, Yutaka (World Bank, Washington, DC, 2012)
Using firm-level data on manufacturing sectors in Africa, this paper addresses how domestic supply constraints and other firm characteristics explain the geographical orientation of firms' exports and the overall market diversification of African manufacturing exports. The degree of market diversification, measured by the number of export destinations, is highly correlated with export intensity at the firm level, and both embody strong scale effects. Technological factors, such as new vintage capital and Internet access, which improve production efficiency and lower export costs, show strong effects on the firm-level export intensity. Some qualitative differences exist between Africa's regional exports and exports to the global markets. Foreign ownership is a significant factor in characterizing the intensity of global exports but not regional exports. The technological factors are significant in both cases, but more so in global exports. Public infrastructure constraints, such as inferior power services and customs delays, seem to have more immediate impacts on regional exports in general, implying the relevance of addressing behind-the-border constraints in fostering regional integration in Africa. Customs efficiency does matter for textile exports to the global markets, underscoring the importance of improving trade facilitation in Africa for competitive participation of African producers in global supply chain industries.